A Critical Analysis of Imam Rabbani Ahmad Sirhindi’s Doctrines on Sufism - Saeyd Rashed Hasan Chowdury; Vahit Göktaş (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2021)
The purpose of this study is to present an analysis of the teachings and ideals of the life and thought of Imam Rabbani Ahmad Sirhindi’s followers inspires the Muslims of the present world to pursue the path of truth, welfare, and justice. We tried to collect data from secondary sources and found that various superstitions entered Sufism when many non-Islamic issues permeated Islam. Imam Rabbani has made tireless efforts in writings and discourses through Sufism to return Islam to its original purity. He was awarded the title of “Reformer of the second millennium” because he first introduced Islamic thought in the history of the Indian subcontinent. On the other hand, Imam Rabbani taught the Waḥdat al-Shuhūd doctrine by criticizing the Waḥdat al-Wujūd doctrine introduced by Ibn ‘Arabī. As he continued the pure tradition of religion by subverting the superstitions of sharia in Islam, he established “Mujaddidiya Tariqa” in the spiritual world and coordinated the sharia-tariqa in Sufism. However, the outcome of our research shows how Imam Rabbani builds equality of status, love, and fraternity and instructs people through Sufism to respect the religion, emotions, and practices of others.